Exploring the creation of an alternative workforce by upskilling pharmacists working in primary care for chronic skin conditions: a qualitative thematic analysis - Sangeeta Punjabi; Ayushi Singh (Future Healthcare Journal)
Introduction: In the post-pandemic era, rapidly growing waiting lists necessitate urgent transformation of service delivery. Chronic skin conditions, such as eczema, psoriasis and hand dermatitis, are widely prevalent, impacting quality of life.1 Skin diseases are the fourth leading cause of non-fatal disease burden world-wide.2 The current situation will continue to worsen if innovative ways of working are not considered.3 Workforce crisis in primary care places the importance of the right person, right setting first time (Getting It Right First Time; GIRFT).4,5 With all pharmacists being prescribers from 2025, the aim of this research is to explore the benefits, barriers and risks of upskilling the clinical pharmacist workforce in general practice to appropriately support management of mild–moderate chronic skin conditions. Material and methods: We used a mixed methodology with prior ethical approval. A qualitative analysis of semi-structured interviews with three groups of stakeholders (five clinical pharmacists in primary care, six GPs and five consultant dermatologists) was performed to evaluate benefits, barriers and risks for the above aim. A quantitative analysis of prospective data of GP referrals to hospital in a month was done to assess mild–moderate chronic skin conditions being accepted. This was supported by data from a follow-up audit analysis (Fig 1).6  Results and discussion: Recordings and transcripts were interpreted from the groups, allowing identification of themes and sub-themes from each group, such as benefits, barriers, risks and a new theme of recommendations. The overarching theme was participants unanimously agreeing that pharmacists are not diagnosticians, but that their strength was in implementing protocols safely and timely follow up of long-term conditions, with the potential added value to reduce GP and secondary care workload. Another strong theme from all groups was that financial constraints in the NHS were a challenge to implementation because pharmacists were needed to meet quality framework targets in primary care.7 Recommendation themes from all groups agreed for a supportive pathway with secondary care input. This includes setting up either a community service that embeds prescribing pharmacists safely, or a post-diagnosis service through advice and guidance with a protocol-driven treatment plan. For the risk theme, all GPs and pharmacists shared the view that pharmacists are a low-risk, safe workforce; however, some consultants had concerns around supervision, delaying appropriate treatment and suboptimal patient outcomes. Quantitative data showed that, out of 250 routine referrals received in a month, 18% were categorised as mild–moderate chronic skin conditions. This aligns with the follow-up audit analysis, which showed that 15% of cases seen by dermatologists could have seen another healthcare professional if available (Fig 1).6 Conclusion: There was a strongly positive response from the participants toward creating an alternative, more sustainable workforce. Current evidence linked to the familiarity of pharmacists with skin conditions remains limited to community pharmacists.8,9 It is prudent to seek a wider expression of interest and develop innovative ways of safe co-working to support management of long-term skin conditions, mirroring the positive impact of clinical pharmacists in managing other long-term conditions.10